The dark side of governance or on the shortcomings of governance networks - Żabiński, Michał (Journal of Public Governance, 2014)
The article deals with the issue of shortcomings of governance. The author presents and discusses the fundamental limitations of governance networks. To that end, he focuses on the issues of trust and communication between network members, network transparency and accountability as well as the problems of management and coordination within a network. He also reviews the impact of governance networks on increasing social inequality.